Case report: SGLT2i, transcutaneous vagus nerve stimulation, and their effects on intrarenal venous flow pattern in HFpEF - Nagai, Michiaki; Dote, Keigo; Kato, Masaya; Sasaki, Shota; Oda, Noboru; Förster, Carola Y. (Frontiers in Neuroscience, 2022)
Renal congestion in heart failure (HF) is a predictor of the prognosis of cardiovascular disease. The effect of sodium-glucose cotransporter 2 inhibitors (SGLT2i) and vagus nerve stimulation (VNS) on renal congestion has not been reported in heart failure (HF). A 77-year-old man with HF with preserved ejection fraction (HFpEF) was referred to our hospital because of poor response to loop diuretics. Echocardiography showed severe tricuspid regurgitation with dilation of the right atrium. Three months after adding SGLT2i, body weight was lost without worsening of renal function. Left and right doppler-derived intrarenal venous flow (IRVF) has been changed from a monophasic to a discontinuous pattern with a systolic interruption. One month later, he discontinued SGLT2i administration at his own discretion. In order to stabilizing autonomic balance, transcutaneous VNS (tVNS) was performed via left ear tragus. One hour after transcutaneous tVNS, ipsilateral IRVF has been dramatically improved from a fusional biphasic to a discontinuous pattern with a systolic interruption. SGLT2i and tVNS may be associated with renal decongestion in HFpEF.